Drawing - In and Outside - Writing - Chorpening, Kelly; Fortnum, Rebecca; Morrens, Peter; Nys, Ans; Voorkamer, Lier (Leuven : Acco, 2012)
Chorpening, Kelly ; Fortnum, Rebecca ; Morrens, Peter ; Nys, Ans ; Nagtzaam, Marc
Voorkamer, Lier, 2012
kunstcatalogus